Chromatography-mass spectrometric study of the chemical composition of Myrtus communis L. leaf essential oil - O. Ye. Matsehorova; V. M. Odyntsova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Myrtus communis is a common species in tropical and subtropical regions. Myrtle is cultivated as an ornamental plant in areas with a temperate climate, such as Ukraine. It was introduced to the Nikitskyi Botanical Garden in 1967. The pharmacological properties of galenic preparations derived from Myrtus communis are primarily determined by the presence of essential oils. Galenic preparations from myrtle leaves have general tonic, antimicrobial (notably demonstrating high bactericidal activity against gram-positive bacteria and antibiotic and resistant strains, Mycobacterium tuberculosis), analgesic, astringent, expectorant, and anti-inflammatory effects. For a comprehensive study of this plant, it is essential to investigate the volatile fractions of its raw material.